Digital holographic microscopy in human sperm imaging - Crha, Igor; Zakova, Jana; Huser, Martin; Ventruba, Pavel; Lousova, Eva; Pohanka, Michal (Journal of assisted reproduction and genetics, 2011)
PURPOSE: The aim of this study was to use digital holographic microscopy (DHM) in human sperm imaging and compare quantitative phase contrast of sperm heads in normozoospermia (NZ) and oligoasthenozoospermia (OAT). METHODS: DHM spermatozoa imaging and repeated quantitative phase shift evaluation were used. Five NZ and 5 OAT samples were examined. Semen samples were examined by semen analysis and processed for DHM. Main outcome measures were maximum phase shift value of the sperm heads. Differences of the phase shift and in NZ and OAT samples were statistically tested. RESULTS: In NZ samples median phase shifts were in the range 2.72-3.21 rad and 2.00-2.15 in OAT samples. Differences among individual samples were statistically significant (p < 0.001) in both groups. Median phase shift according to sperm count was 2.90 rad in NZ samples and 2.00 rad in OAT samples. This difference was statistically significant (p < 0.001). CONCLUSION: Quantitative evaluation of the phase shift by DHM could provide new information on the exact structure and composition of the sperm head. At present, this technique is not established for clinical utility.
Keywords: holografie; Male; Microscopy; Spermatozoa; spermie; Humans; hlavička spermie; Holography; Sperm Head; dospělí; lidé; mužské pohlaví; mikroskopie; Adult